Competitiveness and resilience of the productive districts in Sicily: The behavior of the Sicilian production areas during the economic crisis - Michele Sabatino (Contemporary Economics, 2016)
Resilience' refers to the ability of companies to adapt their strategies in response to economic circumstances that change from time to time. This definition seems appropriate to explain the behavior of the Sicilian productive districts in light of the recent economic crisis. These meta-producing districts of Sicily merit further study, particularly in terms of the concept of resilience and its accompanying economic dynamics. The Sicilian Region has recognized these productive districts, which represent an attempt to use industrial policy to promote various types of mergers among companies. This regional strategy could have been a useful tool to induce the production system to direct its decisions toward forms of integration and inter-company collaboration that would also strengthen the previously begun processes of local development. The crisis reduced any regional policy aspirations and above all decimated the numerous small enterprises that might have represented the backbone of the proto-districts. After an initial methodological and historical reconstruction, the present study focuses on the Sicilian production areas - with particular reference to the industrial area - from the first years of their establishment and regional recognition to those latter years marked by the economic crisis. Thus, we evaluate the degree of resilience of the different districts and their competitive capacities. Arguing about competitiveness and resilience means, on one hand, to understand what the factors are that combine to reduce the vulnerability of a territory and a production system and on the other hand, to identify strategies to increase financing for the same factors that are crucial to a region's economic growth.
Keywords: O1; O25; 330; resilience; productive district; regional strategy; economic crisis